The association between Ehlers‐Danlos syndrome—hypermobility type and gastrointestinal symptoms in university students: a cross‐sectional study. Issue 3 (28th September 2016) - Fikree, A.; Aktar, R.; Morris, J. K.; Grahame, R.; Knowles, C. H.; Aziz, Q.
Abstract: Background: Patients with Ehlers‐Danlos syndrome—hypermobility type (EDS‐HT) have increased prevalence of gastrointestinal (GI) symptoms, particularly reflux and dyspepsia. EDS‐HT is associated with dysautonomia, psychopathology, and chronic pain which can be associated with GI symptoms. The association between GI symptoms and EDS‐HT in a 'non‐patient' population and the effect of the above‐mentioned factors has never been studied. Methods: In a cross sectional study, a hypermobility questionnaire was used to screen university students; further clinical examination established the diagnosis of EDS‐HT. Validated questionnaires assessed for GI, somatic, pain and autonomic symptoms, psychopathology and quality of life (QOL). These were compared in students with and without EDS‐HT; logistic regression analysis examined associations between EDS‐HT, GI symptoms and other variables. Key Results: Of 1998 students screened, 162 were included: 74 EDS‐HT (21.0 years, 53% female) vs 88 Non‐EDS‐HT (21.5 years, 65% female). Compared to non‐EDS‐HT students, EDS‐HT students were more likely to have multiple GI symptoms (41.9% vs 27.3% P =.05), particularly postprandial fullness (34.4% vs 15.9%, P =.01) and early satiety (32% vs 17%, P =.03), greater autonomic ( P <.001) and somatic symptoms ( P =.04) but not psychopathology ( P >.8). The association between EDS‐HT and postprandial symptoms was dependent on autonomic factors but independent of pain and psychopathology. Pain‐related QOL scores were reduced in the EDS‐HT group (80 vs 90, P =.03). Conclusions and Inferences: The previously described association between EDS‐HT, dyspepsia, pain and autonomic symptoms in patients is also present in non‐patient groups. Future studies are necessary to explore the etiological role of connective tissue in GI and extra intestinal symptoms. Abstract : Comparison of GI symptoms in students with and without EDS‐HT. The most common upper GI symptoms in EDS‐HT were abdominal pain (42.6%), postprandial fullness (34.4%), early satiety (31.5%) and bloating (26.4%). However, only postprandial fullness (34.4% vs 15.9%, P =.01) and early satiety (EDS‐HT: 31.5% vs 17%, P =.03) were significantly increased when compared with non‐EDS‐HT students (Table 3). View the podcast on this paper at the following sites: iTunes:https://itunes.apple.com/gb/podcast/neurogastroenterology-motility/id1200500736 YouTube:https://www.youtube.com/watch?v=pa851R412Gg